2008
DOI: 10.1245/s10434-008-9892-3
|View full text |Cite
|
Sign up to set email alerts
|

An Interval >7 Weeks between Neoadjuvant Therapy and Surgery Improves Pathologic Complete Response and Disease–Free Survival in Patients with Locally Advanced Rectal Cancer

Abstract: A neoadjuvant-surgery interval >7 weeks was associated with higher rates of pCR and near pCR, decreased recurrence and improved disease-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
208
4
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(227 citation statements)
references
References 36 publications
11
208
4
4
Order By: Relevance
“…Tulchinsky et al showed that an interval between completion of CRT and surgery of more than seven weeks improved pCR and disease-free survival in patients with rectal cancer. (9) This was confirmed in a meta-analysis that showed that an interval to surgery over eight weeks increased pCR rate by 6%. (10) In our study, 53.8% (7 out of 13) of patients who had surgery 12 weeks after the completion of CRT achieved pCR.…”
Section: Discussionmentioning
confidence: 82%
“…Tulchinsky et al showed that an interval between completion of CRT and surgery of more than seven weeks improved pCR and disease-free survival in patients with rectal cancer. (9) This was confirmed in a meta-analysis that showed that an interval to surgery over eight weeks increased pCR rate by 6%. (10) In our study, 53.8% (7 out of 13) of patients who had surgery 12 weeks after the completion of CRT achieved pCR.…”
Section: Discussionmentioning
confidence: 82%
“…The authors found both trials underpowered in terms of number of randomized patients to detect the significance between two regimens. Another conclusion that Neoadjuvant therapy for rectal carcinoma Marmara Medical Journal 2015; 28 (Special issue 1): [16][17][18][19][20] quality of life documentation was poor in Polish study and this lead no significant difference between two arms.…”
Section: Comparison Of the Regimensmentioning
confidence: 89%
“…pCR has been considered as a surrogate marker of improved responses and EFS in rectal adenocarcinoma (11). These studies emphasizes on the addition of chemotherapy pre or post CRT to improvise pCR rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, both trials showed improved in local control rates without DFS or OS benefit. The addition of oxaliplatin or biological therapy to CRT regimen has not been consistently associated with higher response rates and definitely not without increasing toxicity (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%